Development of disciplines based manufacturing information system for ship construction company - Bozorgi Rad, Seyed Yaser (2008)
New models and facilities are needed for the growing economy and the very hard competition that it brings with it. Among the many models of information systems two have been very strong: Workflow Management Systems (WFMS) and Enterprise Resource Planning (ERP) systems. While both systems are very strong for integration and other management applications, a complete understanding of these methods is still lacking. This research first aims at the importance of organization integration and the structure of these two models is compared. Subsequently a comprehensive analogy of WFMS and ERP systems and the major difficulties in integration of the models in application is taken into account. In the end a case study is performed on a major Iranian ship company called SADRA. The current workflow in this company is first evaluated and put under major scrutiny. In the end a new framework for the work flow of this company is developed based on the basic concepts of ERP and WFMS. This Frame work reduces a major amount of redundancy in the data patterns. The final result of this study is a Discipline-Based Manufacturing Information System for a Ship Construction Company.